TRIM56: a promising prognostic immune biomarker for glioma revealed by pan-cancer and single-cell analysis - Wang, Bingcheng; Wang, Zhihai; Li, Yuchen; Shang, Zehan; Liu, Zihao; Fan, Hao; Zhan, Rucai; Xin, Tao (Frontiers in Immunology, 2024)
Tripartite-motif 56 (TRIM56) is a member of the TRIM family, and was shown to be an interferon-inducible E3 ubiquitin ligase that can be overexpressed upon stimulation with doublestranded DNA to regulate interferon gene factor (STING) to produce type I interferon and thus mediate innate immune responses. In this study, we investigated the relationship between TRIM56 gene expression and prognostic value in pan-cancer. Then we explored the differential expression of TRIM56 in different subtypes of gliomas and verified its role as an independent prognostic factor in gliomas. Subsequently, the correlation between TRIM56 and immune infiltration was explored, functional analysis was performed, and some cell experiments and animal experiments were used to verify. In addition, we used single-cell analysis to explore the effect of TRIM56 expression on cell communication between glioma cells and non-tumor cells, and constructed a signature based on cell markers of tumor cells with high TRIM56 expression to better predict the prognosis of cancer patients.Background: Tripartite-motif 56, a factor that promotes interferon production, in tumors is inconclusive. At present, the role of TRIM56 in glioma is rarely reported. This study aims to investigate the prognosis of TRIM56 in glioma, and the relationship between TRIM56 expression level and tumor immune microenvironment and tumor cell communication.